HUKUM MENJUAL HAK SUARA PADA PEMILUKADA DALAM PERSPEKTIF FIQH SIYÂSI - Umar, M Hasbi (al-'adalah, 2014)
Abstract: Voting Right on Election In the Perspective of Fiqh Siyâsi (Political Law). Factually, the political condition which is emerging today is really loaded with the political interests, money politic becomes a trend in every Direct Local Election (Pemilukada); voting right is traded. The practice of money politic has occurred in many areas. This violation is very anxious since it is utilized as an instrument of winning in direct election. Consequently, the suffrage of citizens is hijacked by the interest of the candidate. The practice of money politic can occur during the campaign and prior to the vote. Unfortunately, in some cases, the election officers also involve in such practice. Then there is a sale and purchase of votes which led to fraud in determining and stipulating of votes acquisition and potentially might alter the electability of candidates. The real loss of money politic is the loss of dignity of citizens’ voting right. The voting right would only be a political commodity amid the competition among candidates. The sovereignty of the people becomes meaningless since money has been played in which subsequently will be detrimental to them. For the long run, the practice of corruption is likely to flourish. A position which is obtained by huge capital becomes justification for getting back that capital while occupying political position. Fraud in the election is not only morally wrong, but a form of law transgression. The practice of selling and purchasing of votes in the electionist classified as risywah which is strongly prohibited in Islam. Abstrak: Hukum Menjual Hak Suara pada Pemilukada dalam Perspektif Fiqh Siyâsi. Politik uang (money politic) menjadi tren di setiap Pemilukada; hak suara diperdagangkan. Praktik ini terjadi di banyak daerah. Pelanggaran seperti ini sudah sangat memprihatinkan karena digunakan sebagai alat menang dalam pemilihan langsung. Akibatnya, hak pilih warga dibajak oleh kepentingan kandidat. Praktik money politic dapat terjadi selama kampanye dan sebelum pemungutan suara. Sayangnya, dalam beberapa kasus, petugas pemilu juga terlibat dalam praktik tersebut. Lalu ada jual beli suara yang menyebabkan penipuan dalam menentukan dan menetapkan suara sehingga berpotensi bisa mengubah elektabilitas calon. Kerugian nyata money politic adalah hilangnya martabat warga Negara. Hak suara hanya akan menjadi komoditas politik di tengah persaingan antar kandidat. Kedaulatan rakyat menjadi tidak berarti. Untuk jangka panjang, praktik korupsi cenderung berkembang. Sebuah posisi yang diperoleh dengan modal besar menjadi pembenaran untuk mendapatkan kembali modal yang sementara menduduki posisi politik. Praktik jual beli dan suara dalam kampanye diklasifikasikan sebagai risywah (suap) yang sangat dilarang dalam Islam.